2018
DOI: 10.5539/gjhs.v10n12p127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristic of Dietary Supplement Users in Malaysia: Data From the Malaysian Adult Nutrition Survey (MANS) 2014

Abstract: BACKGROUND: There has been an increase trend of dietary supplements intake among Malaysians over the last decade. The aim of this study was to determine the prevalence and characteristic of dietary supplements users among adults in Malaysia. METHODS: Data of 3000 respondents aged 18–59 years from the Malaysian Adult Nutrition Survey (MANS) 2014 were utilized. A multi-stage stratified sampling method was employed and eligible respondent from each household was selected using Kish method. Validated que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…A study in Kuwait indicated that educated mothers have better access to health information, implements good health practices, and participated actively in family health decisions [ 60 ]. The greater likelihood of women, older aged adults and those with higher education level to consume dietary supplements as indicated by Mohd Zaki et al [ 61 ], could also explain the greater use of community pharmacy among these group of people in our study. Hence, it is possible to conclude that higher level of education serves as an important determinant of community pharmacy use.…”
Section: Discussionsupporting
confidence: 50%
“…A study in Kuwait indicated that educated mothers have better access to health information, implements good health practices, and participated actively in family health decisions [ 60 ]. The greater likelihood of women, older aged adults and those with higher education level to consume dietary supplements as indicated by Mohd Zaki et al [ 61 ], could also explain the greater use of community pharmacy among these group of people in our study. Hence, it is possible to conclude that higher level of education serves as an important determinant of community pharmacy use.…”
Section: Discussionsupporting
confidence: 50%
“…According to Alhomoud et al (2016), the prevalence was expected to increase in developing countries due to the widespread use of the DS and increase the trust in the needs of dietary supplementation (14). Malaysia is one of the developing countries that reported was showing an increasing number of DS consumers, especially among adults as reported from the Malaysian Adult Nutrition Survey (MANS) 2014 (9). Consequently, the number also may increase among college students as evidenced by Al-Naggar and Chen (2011) and Haque et al (2016) (3,10).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous findings indicated positive results especially in western countries; there is scarce information on Asian countries. Little is known on the use of dietary supplements among students (Sien et al, 2014) and in Malaysia as well (Mohd Zaki et al, 2018). There is an assumption which indicates the intake of DS is mainly done by people who lack in nutrients such as older people, pregnant women and individual with health problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Asian, South Korea showed high demands in consuming DS with an average of 60% people consume ginseng, multivitamins, glucosamine, probiotics and vitamin C (Ock, Hwang, Lee, Song, & Ock, 2010). While in Malaysia; through its first National Nutrition Survey by the Ministry of Health in 2008, only 25% of the adult population consumes DS (Mohd Zaki et al, 2018). However, according to Malaysian Dietary Supplement Association (MDSA); the Malaysian market for DS continues to grow progressively despite the weak business activity and low acceptance among consumers (Birruntha, 2019).…”
Section: Introductionmentioning
confidence: 99%